The Role of Teachers in Encouraging Digital Literacy Capabilities in Rural High Schools of Bandung - Rusmana, Agus; Rizal, Edwin; Saepudin, Encang (TEMALI : Jurnal Pembangunan Sosial, 2023)
The anti-hoax social movement was initiated online in Indonesia by relying on the netizens’ togetherness to fight the spread of hoaxes in a virtual world by identifying and reporting hoaxes and promoting accurate information and critical thinking skills. Digital scoping is carried out by reporting hoaxes that are spread on social media, while counter-narrative actions take the form of checking facts and disseminating disclaimers. The level of participation of netizens in the anti-hoax movement is relatively high. They voluntarily participate in various anti-hoax campaigns. Teachers in Bandung high schools have been allowed to pick and implement proposals and solutions based on their students’ needs and requirements for digital literacy. This technique has effectively surmounted the barriers to students’ digital literacy abilities, preventing them from causing problems that students, in particular, feel during studying. As a result, kids can select which news can be believed and which is a scam. The strategy used in education to address students’ digital literacy skills has increased students’ digital literacy skills, allowing them to learn more quickly and accurately. Teachers can also help pupils develop their digital literacy skills so that other students are not left behind in understanding learning material.